Teknopreneurship, Budaya, dan Spiritualitas di Era Kecerdasan Buatan: Perspektif Budaya Terhadap Inovasi Berorientasi Manusia - Albaburrahim Albaburrahim; Mochamad Arifin Alatas; Moh. Badruddin Amin (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
The rapid development of artificial intelligence (AI) has significantly changed the dynamics of technology entrepreneurship and digital innovation across various sectors. However, technological development often places greater emphasis on efficiency and economic growth, while neglecting the cultural and spiritual dimensions that influence human-centered innovation. The purpose of this study is to explore the relationship between technology entrepreneurship, culture, and spirituality in the era of artificial intelligence from a cultural perspective. This study uses a qualitative approach with conceptual and literature-based methods to analyze relevant academic sources related to AI-based entrepreneurship, cultural values, and spiritual ethics. The findings indicate that artificial intelligence plays a crucial role in expanding technopreneurial innovation. First, artificial intelligence (AI) drives technopreneurial innovation. Second, culture is a defining value in human-oriented technological innovation. Third, spirituality defines the ethical values ​​of responsible technology entrepreneurship in the use of artificial intelligence (AI). Therefore, the integration of technology entrepreneurship, culture, and spirituality offers a holistic framework to guide sustainable and responsible technology development in the era of artificial intelligence.